EGF receptor family: targets for improving cancer therapy - Burgess, Tony (Henry Stewart Talks, 2021)
EGFR family members and cancer, EGFR signalling in the oncogenic processes, EGFR family structural biology, ErbB2 and ErbB3 signalling, EGFR dimer oligomerization, PI3 kinase pathway, E-cadherin, EGFR inhibitors and antagonists, Colon cancer treatments